Development of a Culture-Based Coding E-Book from North Sumatera to Enhance Computational Thinking - Niken Farida; Hilma Mithalia Shalihat; Syartika Sri Wahyuni (LP. Ma'arif Janggan Magetan, 2025)
This study aimed to develop a North Sumatra culture-based coding activity e-book to enhance CT skills in early childhood education. The ADDIE development model consisting of the analysis, design, development, implementation, and evaluation phases, was employed and involved 160 children from nine kindergartens in Medan City. Expert validation indicated that the e-book was feasible for instructional use, with scores exceeding 80%, while the CT measurement instrument demonstrated high reliability with a Cronbach’s Alpha of 0.744. Small- and large-scale trials consistently showed significant improvement in children’s CT abilities, confirmed by the Wilcoxon test (Z = –8.901; p < 0.05). These results highlight that integrating local culture into coding activities supports CT development and simultaneously strengthens cultural values from an early age. The findings reinforce the importance of contextualized digital learning media that align with the goals of 21st-century education and foster cultural identity. The study further suggests that culture-based coding media can serve as an innovative learning resource to enrich PAUD (early childhood) instruction. Future research is encouraged to apply this concept in other cultural settings and include additional interactive features—such as animation, audio, gamification, or augmented reality—to enhance children’s engagement and learning outcomes. Long-term investigations are also needed to examine CT development over extended periods, along with broader collaboration with teachers and early childhood institutions to support continuous refinement of the media based on classroom needs.